Impact of Coronavirus disease (COVID-19) pandemic on health professionals - Sethi, Bilal Ahmed (Pak J Med Sci, 2020)
OBJECTIVE: Recognizing the huge potential ramifications of COVID-19 pandemic, this study explores its impact on health professionals personally and professionally along with the associated challenges. METHODS: A descriptive cross-sectional qualitative survey was conducted from March-April 2020. Participants included health professionals from various disciplines in both public and private-sector institutions of Pakistan. The sample size was not predetermined, and an iterative approach of simultaneous data collection and analysis was taken until data and time saturation were reached. Thematic analysis of the qualitative data was carried out by two analysts. RESULTS: Two hundred and Ninety health professionals responded. They reported an impact on their mental, physical and social well-being. The clinicians mentioned facing an unprecedented workload in overstretched health facilities, while those in academia become engaged with planning/providing emergency remote teaching for the students affecting work-life balance. Some challenges associated with work-from-home and in the hospitals were identified. CONCLUSION: During COVID-19, the health professionals are anxious, overworked and financially unstable while planning, creating and caring for others and their families. We need to support them to do their jobs, be safe and stay alive. Future research should explore the fears and coping strategies of health professionals during pandemics.